2010
DOI: 10.3109/02699200903440983
|View full text |Cite
|
Sign up to set email alerts
|

Automatic method of pause measurement for normal and dysarthric speech

Abstract: This study proposes an automatic method for the detection of pauses and identification of pause types in conversational speech for the purpose of measuring the effects of Friedreich's Ataxia (FRDA) on speech. Speech samples of approximately 3 minutes were recorded from 13 speakers with FRDA and 18 healthy controls. Pauses were measured from the intensity contour and fit with bimodal lognormal distributions using the Expectation-Maximization algorithm in Matlab. In the speakers with FRDA, both modes in the paus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Duffy’s [4] observations in PPA are highly consistent with studies examining acquired AOS subsequent to stroke [22]. Here, we focus on syllable segregation and lexical stress, as measurement from digital recordings of speech is straightforward, does not rely on expert judgments, and can be implemented in automated software routines [24], [25], [26], [27], [28], which standardize and streamline data collection and analysis.…”
Section: Introductionmentioning
confidence: 75%
“…Duffy’s [4] observations in PPA are highly consistent with studies examining acquired AOS subsequent to stroke [22]. Here, we focus on syllable segregation and lexical stress, as measurement from digital recordings of speech is straightforward, does not rely on expert judgments, and can be implemented in automated software routines [24], [25], [26], [27], [28], which standardize and streamline data collection and analysis.…”
Section: Introductionmentioning
confidence: 75%
“…This cutpoint is similar to the value found to differentiate groups in prior studies (32). Although PPT does not differentiate between speech breathing pauses and non-breathing pauses, the 300 ms minimum pause threshold used in this study has been previously shown to be an optimal threshold for obtaining stable estimates of pausing in speakers with ALS (33) and prior research has shown that breathing-related pauses are typically over 150–250 ms in duration at normal speaking rates (34, 35). Nonetheless, our pause data may include some non-breathing pauses in addition to breathing pauses.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the current pause (silence) approaches [24,27,29] determine a single intensity threshold based on the entire sample, whereas a moving window approach may ultimately prove more reliable and accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity threshold was set to 0.65 of the distance between the reference intensity (equal to 0.95 of the maximum intensity) and the floor intensity (minimum). The reference intensity selection of 0.95 of the maximum intensity has been found to be more robust than the use of the maximum, median, or modal intensities due to irregular bursts of energy that often occur with sporadically loud syllables or short phrases in spontaneous speech (e.g., emphatic stress) [24]. Analysis yielded the following measures: total number of silences, mean silence time, SD of silence length, total speech time, and speech-to-silence ratio.…”
Section: Methodsmentioning
confidence: 99%